DETERMINATION OF EMISSIONS FROM PROTOTYPE ENGINE FOR GENERATION OF POWER FROM EXHAUST GAS OF GASOLINE GENERATOR (FUDMA JOURNAL OF SCIENCES, 2023)
The capacity to produce power from the gases emitted from the exhaust of gasoline generator is  a remarkable and admirable accomplishment. But using the prototype engine to provide this power leads to obstruction in the exhaust gas flow line, which tends to affect exhaust gas emissions. Regarding this, emissions from the prototype engine and the lone or sole generator in this research were assessed at various generator speeds and loads. The study found that the emissions of  carbon monoxide, carbon dioxide and hydrocarbon  from the sole generator were 4.72 %, 4.36 %, and 76 ppm, respectively, while those from the prototype engine were 4.81 %, 4.41 %, and 88 ppm. This was at the minimum generator speed of 1000 rpm and load of 1200 W.  The prototype engine's carbon monoxide, carbon dioxide and hydrocarbon   emissions were 2.51 %, 4.97 %, and 34 ppm, respectively, while the sole generator's carbon monoxide, carbon dioxide and hydrocarbon  emissions  were 2.39 %, 4.89 %, and 32 ppm  respectively, at the maximum generator speed of 5000 rpm and load of  2800 W. At minimum generator speed of 1000 rpm and load of 1200 W, the carbon monoxide, carbon dioxide and hydrocarbon  emissions are, however, slightly higher in the prototype engine than the sole generator by 9%, 5 %, and 12 ppm respectively, and at maximum generator speed of 5000 rpm and load of 2800 W, the carbon monoxide, carbon dioxide and hydrocarbon   emissions are, respectively, slightly higher...
Keywords: Emissions; exhaust gas; generator; load; prototype engine; speed; sole generator